Analisis Kesulitan Pembelajaran Daring Pada Mahasiswa Fakultas Ekonomi Universitas Negeri Padang - Jerry Zulhendri (Universitas Negeri Padang, 2022)
This study aims to analyze the factors of online learning difficulties in students of the Faculty of Economics, Universitas Negeri Padang. Internal factors of online learning difficulties include: (physical health, spiritual health, ready to face obstacles and obstacles, a less supportive family economy, activeness in learning, interest in learning, desire to learn and high confidence in learning) external factors from Difficulties in online learning include: (enthusiasm in learning, having encouragement in learning, readiness to minimize obstacles and obstacles, uncomfortable home conditions so that children find it difficult to study with focus, material delivered by lecturers in online lectures, learning facilities and infrastructure and life in society). The sampling technique was proportional random sampling. The data collection technique used questionnaire. The analytical method used descriptive analysis and factor analysis. Based on the results of factor analysis, there are four factors that influence learning outcomes using e-learning, namely physiological factors, non-social factors, psychological factors and social factors. The dominant factor of online learning difficulties in students of the Faculty of Economics, Padang State University is physiological factors. For students, in order to understand the material given by the lecturer in e-learning.